2019
DOI: 10.1111/vsu.13155
|View full text |Cite|
|
Sign up to set email alerts
|

Short‐ and long‐term outcome after transcondylar screw placement to treat humeral intracondylar fissure in dogs

Abstract: Objective: To describe the postoperative complications and long-term functional outcome after surgical management of humeral intracondylar fissure (HIF) by transcondylar screw (TCS) placement. Study design: Retrospective study. Sample population: Nineteen dogs (26 elbows) Methods: Medical records (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009) were reviewed for dogs with a diagnosis of HIF according to results of computed tomography and treated by TCS placement at a single referral institution. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 44 publications
3
61
2
Order By: Relevance
“…A recent study looking at the long-term outcome following placement of a transcondylar lag screw via a lateral approach reported that dogs which sufered SSI had a higher likelihood of an unsatisfactory outcome as assessed by owner questionnaire. 19 This diference in outcome may be related to the higher number of dogs with SSI (11/26) compared with our report (2/14), to the difering surgical techniques, or to both factors.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…A recent study looking at the long-term outcome following placement of a transcondylar lag screw via a lateral approach reported that dogs which sufered SSI had a higher likelihood of an unsatisfactory outcome as assessed by owner questionnaire. 19 This diference in outcome may be related to the higher number of dogs with SSI (11/26) compared with our report (2/14), to the difering surgical techniques, or to both factors.…”
Section: Discussioncontrasting
confidence: 66%
“…Force plate data have recently been reported for dogs with HIF treated with a transcondylar lag screw placed via a lateral approach, and this report found reduced peak vertical force in treated limbs, with similarly reduced values in the limbs treated for humeral condylar fracture. 19 We found no relationship between outcome and screw angulation or eccentricity. Our range of screw angulation was similar to previous reports on lateral humeral condylar fractures and HIF.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Sixty‐nine percent of dogs had reduced elbow ROM at the first follow‐up, which decreased to 33% at last radiographic follow‐up; reduced ROM is not unexpected after humeral articular fracture repair 33 . Despite reduced joint mobility, only minimally detectable lameness was present at first and last follow‐ups, and the outcome was excellent in 87% of dogs according to the long‐term CBPI and questionnaire results.…”
Section: Discussionmentioning
confidence: 92%
“…Reported mean surgical duration for luoroscopic transcondylar screw placement is 35 minutes (range 20-70), 19 while the reported mean duration for conventional transcondylar screw placement is 47 minutes (range 20-185). 20 This, when considered in combination with our collected times, highlights that the additional time required to perform luoroscopy may be compensated for by greater certainty or conidence in where the drill should be placed in the clinical setting, as there is a consequence to inaccurate drilling, which is not observed in the model setting. Limitations in this study included the number of participants and sample sizes, which were restricted because of the ethical considerations of using ionising radiation in an experimental study.…”
Section: Discussionmentioning
confidence: 81%